2021
DOI: 10.1530/rep-20-0264
|View full text |Cite
|
Sign up to set email alerts
|

FGF2/FGFR signaling promotes cumulus–oocyte complex maturation in vitro

Abstract: Fibroblast growth factor 2 (FGF2), a member of FGF family, binds with FGF receptors (FGFR) to initiate biological functions in various somatic cells. However, little is known regarding the role of FGF2/FGFR on oocyte meiosis. In this study, we investigated expression patterns and functions of FGF2/FGFR during in vitro maturation (IVM) of mouse cumulus-oocyte complexes (COCs). Among four FGFRs, Ffgr1 was the most abundant in COCs. The transcripts for Fgf2 and Ffgr1 in COCs increased during IVM. Ffgr1 was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 17 publications
1
15
1
Order By: Relevance
“…This suggests that FGF2 exerts suppressive effects on cumulus expansion in cattle. In contrast, in a recent murine study, it was reported that FGF2 promotes cumulus expansion in terms of the degree of expansion and expression of related genes (Du et al, 2021). In addition, the present findings suggest that FGF signals, other than FGF8, exert suppressive effects on the expression of cumulus expansion-related genes in mice.…”
Section: Discussioncontrasting
confidence: 97%
“…This suggests that FGF2 exerts suppressive effects on cumulus expansion in cattle. In contrast, in a recent murine study, it was reported that FGF2 promotes cumulus expansion in terms of the degree of expansion and expression of related genes (Du et al, 2021). In addition, the present findings suggest that FGF signals, other than FGF8, exert suppressive effects on the expression of cumulus expansion-related genes in mice.…”
Section: Discussioncontrasting
confidence: 97%
“…In cattle, inhibition of FGF signaling on the day of IVF inhibited blastocyst formation, whereas supplementation of FGF2 following IVF increased blastocyst formation [75]. In mice, FGF2 was reported to have an autocrine/paracrine action to promote cumulus expansion and oocyte meiotic maturation [76]. Although FGF 11 expression was more abundant in cumulus cells of large compared to small follicles, FGF 11 is not secreted and its biological function in the cumulus cell/oocyte complex is not currently known [63].…”
Section: Cumulus Cell Transcriptomementioning
confidence: 99%
“…The cumulus expansion of the COCs and the proportion of PBE are two key indicators of the porcine oocytes developmental competence ( Lan et al, 2020 ; Du et al, 2021 ). Our results revealed that oocytes exhibited a lower proportion of PBE with impaired expansion of cumulus cells following arsenite treatment, indicating that arsenite impairs the oocyte meiotic maturation and developmental competence.…”
Section: Discussionmentioning
confidence: 99%